Physics and Chemistry of Carbon-Based Materials Basics and Applications - Kubozono, Yoshihiro; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book includes the fundamental science and applications of carbon-based materials, in particular fused polycyclic hydrocarbon, fullerene, diamond, carbides, graphite and graphene etc. During the past decade, these carbon-based materials have attracted much interest from many scientists and engineers because of their exciting physical properties and potential application toward electronic and energy devices. In this book, the fundamental theory referring to these materials, their syntheses and characterizations, the physical properties (physics), and the applications are fully described, which will contribute to an advancement of not only basic science in this research field but also technology using these materials. The book's targets are researchers and engineers in the field and graduate school students who specialize in physics, chemistry, and materials science. Thus, this book addresses the physics and chemistry of the principal materials in the twenty-first century. .
1. Graphite and Intercalated Compound Superconductors: Atomic and Electronic Structures -- 2. Physics of graphene: basic to FET application -- 3. Physics of heavily-doped diamond: electronic states and superconductivity -- 4. Physics of carbon nanotubes and new type of carbon network materials: Electronic and magnetic properties -- 5. Electronic and geometric structures of cluster encapsulated fullerenes -- 6. Superconductivity of carbides -- 7. Organic chemistry of p-conjugated polycyclic aromatic hydrocarbons: Acenes and Phenacenes -- 8. Transistor Application and Intercalation Chemistry of p-Conjugated Hydrocarbon Molecules -- 9. Nano-structure control of crystalline organic thin films by a solution process -- 10. Solar cell applications of p-conjugated molecules.
Keywords: Optical materials; Condensed matter; Physical chemistry; Chemistry, Organic; Optical Materials; Condensed Matter Physics; Physical Chemistry; Organic Chemistry